Pengaruh resiliensi akademik terhadap prestasi belajar siswa dan implikasinya dalam Bimbingan dan Konseling - Putri, Fovi; Yendi, Frischa Meivilona (Counseling and Humanities Review, 2023)
This research is motivated by the many obstacles or difficulties students encounter during the learning process. After carrying out the learning process within a certain period of time, the results are obtained, the results of these achievements are referred to as learning achievement, one of the factors that influence learning achievement is academic resilience. The purpose of this research is to test whether there is a significant influence between academic resilience and student achievement at SMA N 11 Padang. The type of research used is correlational quantitative. The sample of this research was the students of SMA N 11 Padang, totaling 255 people who were selected using a stratified random sampling technique. The instrument used is the scale of academic resilience and learning achievement. Data were analyzed using descriptive and regression analysis techniques. The results of the study revealed that there was a significant influence between academic resilience and student achievement as seen from the Anova F table, the count was 13.242 and a significance of 0.000 which means <0.05.